2000
DOI: 10.1023/a:1001922004459
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Family functioning was investigated as a mediator between interparental conflict and adolescent depressed mood among adolescents living in two-parent and divorced families. Data were collected three times, with one year intervals. At the initial interview, adolescents were, on the average, 15.5 years old. Two types of interparental conflict were assessed: interparental conflict involving arguments about the adolescent, and arguments focused on the parents' behaviors. The results confirmed that family functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…In contrast, boys’ perceptions of the family did not predict later anxiety symptoms. These findings are consistent with theory and research that indicate that, during adolescence, girls may be more sensitive to family stress and conflict than boys (Davies & Lindsay, 2004; Unger, Brown, Tressel, & McLeod, 2000). Girls also tend to be more enmeshed in the family than boys during adolescence (Gore, Aseltine, & Colten, 1993) and subsequently may be more negatively affected by family problems than are boys.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, boys’ perceptions of the family did not predict later anxiety symptoms. These findings are consistent with theory and research that indicate that, during adolescence, girls may be more sensitive to family stress and conflict than boys (Davies & Lindsay, 2004; Unger, Brown, Tressel, & McLeod, 2000). Girls also tend to be more enmeshed in the family than boys during adolescence (Gore, Aseltine, & Colten, 1993) and subsequently may be more negatively affected by family problems than are boys.…”
Section: Discussionsupporting
confidence: 90%
“…This oversight is unfortunate given that during adolescence, girls have closer relationships with their family and are more sensitive to disruptions and conflict in their family environment in comparison to boys (Davies & Lindsay, 2004; Shek, 2007; Unger, Brown, Tressel, & McLeod, 2000). In addition, during adolescence, boys are expected to behave more autonomously and independently and to be less enmeshed in the family in comparison to girls (Papini & Micka, 1991; Shek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The current literature yielded mixed findings on the moderating role of gender in the relationship between inter-parental conflict and attitudes towards marriage. For example, there are evidences which suggested that females are more vulnerable to inter-parental conflict than males (Cummings & Davies, 2011;Gore, Aseltine, & Colten, 1993;Unger, Brown, Tressell, & McLeod, 2000). However, there are also counter arguments which claimed that males are at greater risk for maladjustment than females following parental divorce (Branje, Hale, Frijns, & Meeus, 2010;Brown & Portes, 2006).…”
Section: Mechanism Affecting Attitudes Towards Marriage Among Adolescmentioning
confidence: 99%
“…Interparental conflicts hold implicit particularities which can decrease the quality level of family operation, especially when they are not resolved and thus limit the opportunity for adolescents to learn how to efficiently resolve problems, or even compromise the development of resolution strategies. Moreover, it also decreases the perception of parental support and communication skills, increases the establishment of dysfunctional ties between adolescents and their parents, and also reduces the possibility of providing adolescents with the understanding of family as a cohesive support system (Unger, Brown, Tressell, & McLeod, 2000).…”
mentioning
confidence: 99%
“…It became evident that the existence of conflict between the couple was associated to the development of internalization problems in the children, such as anxiety and depression as well as externalization problems such as aggressive behavior. On the other hand, Unger et al (2000), in a study done with a sample of 107 adolescents between the ages of 12 and 18, from divorced as well as intact families, had the objective of studying the family and the influence of interparental conflicts on the psychological adjustment of the children, it was found that interparental conflicts have a very close connection with the depressed state of children belonging not only to divorced but also intact families. According to O'Donnell, Moreau, Cardemil and Pollastri (2010), the development of depressive symptomatology can result from negative alterations to the family environment, which surges from parental conflicts, interacting with the children's pessimistic cognitive style.…”
mentioning
confidence: 99%